Development and Validation of the Pediatric Well-Being Picture Scale© Using a Mixed-Methods Research Design - Judith Quaranta; Rosa Darling; Mei-Hsiu Chen; Julia DeMartino; Madison Kozlowski (Nursing Reports)
Background/Objectives: Decreased well-being may be a precursor to mental health challenges. Mental health visits for 5–11-year-old children increased by 24% from 2019 to 2020. COVID-19 led to record high levels of anxiety and depression in young children. This highlights the need for early identification and intervention of decreased well-being to prevent progression to potential mental health issues. The purpose of our research was to develop the Pediatric Well-Being Picture Scale© (PWBPS©), the first picture-based screening tool for ages 8–11 years, accessible to children regardless of their literacy, language skill, and developmental levels, allowing for quick screening for early referral and intervention. Methods: The mixed-methods research design included focus groups and one-on-one interviews for content and face validity, test/retest reliability, convergent validity, and exploratory factor analysis. Subjects were recruited from public elementary schools. Results: The numbers of participating subjects were as follows: N = 17 for focus groups; N = 12 for one-on-one interviews; N = 50 for test/retest reliability; and N = 237 for convergent validity. Thematic analysis resulted in a 10-item, 3-point picture-based Likert scale. The test/retest reliability demonstrated strong correlations, with an ICC of 0.823 (95% CI [0.690, 0.905]). The Cronbach’s alpha for all the administrations was 0.74, 0.74, 0.84, and 0.89. The convergent validity demonstrated correlation with the validated KIDSCREEN-10. The Spearman’s correlation was 0.64 (95% CI as [0.55, 0.71]). The cutoff for the PWBPS© was 18.5, which correlated to a score of 22 on the KIDSCREEN-10. All the items loaded on one component. Conclusions: These findings demonstrate that the PWBPS© is valid and reliable, allowing for quick and accurate assessments of children’s well-being and allowing for early intervention, which is key to reducing the negative effects of poor mental well-being.